The Influence of Digital Marketing of Banking Products, Technology Acceptance Model, and Theory of Planned Behavior on Consumer Purchase Intention in the Pahlawan Village Community, Batu Bara Regency - Fitra Arlina Nasution; Dewi Nurmasari Pane (International Journal of Management, Economic and Accounting, 2025)
This research aims to analyze the influence of digital marketing on consumer purchase interest in banking products in Pahlawan Village, Batu Bara Regency. With the increasing penetration of the internet and the use of social media in rural areas, banks are beginning to adopt digital marketing strategies as a means to reach potential customers more effectively and efficiently. Through a quantitative approach with the distribution of questionnaires to the village community, this research examines the extent to which elements of digital marketing can shape perceptions, interest, and ultimately drive the intention to purchase banking products. The research results show that digital marketing has a significant influence on consumer purchase interest, particularly in aspects of trust, ease of access to information, and personalization of marketing messages. These findings provide strategic implications for financial institutions in designing marketing approaches that are relevant and adaptive to the characteristics of rural communities.